ICT capital and productivity growth - Hubert Strauss; Besik Samkharadze (EIB Papers, 2011)
ICT capital is an important driver of productivity growth. Using data from the EUKLEMS growth accounts, we show that ICT has made smaller contributions to labour productivity growth in the EU-15 than in the US, both at the macro level and at the level of individual sectors. At the same time, progress in productive efficiency - as measured by total factor productivity (TFP) growth - sharply declined in Europe and has remained weak since the mid-1990s whereas the US has seen acceleration in TFP. The near-stagnant TFP in market services in the EU-15 is particularly worrying. In both the EU-15 and the US, the growth contributions from ICT are found to be smaller than those from TFP. However, our empirical analysis suggests that the full effect of ICT capital on productivity is larger than what the growth accounts suggest because many ICT benefits occur with a delay.
Keywords: 330